2008
DOI: 10.1292/jvms.70.1031
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Persistent Salmonella Enteritidis Strains in Two Integrated Broiler Chicken Operations of Korea

Abstract: ABSTRACT. The objectives of the study were to investigate the phenotypic and genotypic characterization of the persistent Salmonella Enteritidis (S. Enteritidis) isolates in two integrated broiler chicken operations, with attention focused mainly on the epidemiological approach. In the distribution of virulence genes, Salmonella enterotoxin (stn), invading host cell (invA), and Salmonella plasmid virulence (spvC) genes were widely distributed among the S. Enteritidis irrespective of their source of isolation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
4
1
1
Order By: Relevance
“…The majorities (98.7%) of ESBLs‐producing Salmonella isolates in this study harbored at least one virulence gene, which highlights their potential pathogenesis and the risk associated with this pathogen in retail chickens in China. Compared to the results of other studies on Salmonella (Huehn et al., ; Kwag et al., ), the detection percentage of virulence genes among ESBLs‐producing Salmonella in this study were different compared to other studies. Although virulence genes, such as sip A, sod C1, sop E2, rck , spv C, msg A, and pef A, were commonly detected in some foodborne Salmonella strains linked to human salmonellosis cases, clinical diarrhea and infections, these genes were rarely detected in our isolates (Capuano et al., ; Huehn et al., ; Mezal et al., ; Osman, Marouf, & Alatfeehy, ; Zhang et al., ; Zou et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…The majorities (98.7%) of ESBLs‐producing Salmonella isolates in this study harbored at least one virulence gene, which highlights their potential pathogenesis and the risk associated with this pathogen in retail chickens in China. Compared to the results of other studies on Salmonella (Huehn et al., ; Kwag et al., ), the detection percentage of virulence genes among ESBLs‐producing Salmonella in this study were different compared to other studies. Although virulence genes, such as sip A, sod C1, sop E2, rck , spv C, msg A, and pef A, were commonly detected in some foodborne Salmonella strains linked to human salmonellosis cases, clinical diarrhea and infections, these genes were rarely detected in our isolates (Capuano et al., ; Huehn et al., ; Mezal et al., ; Osman, Marouf, & Alatfeehy, ; Zhang et al., ; Zou et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…The spvC and rck genes were found in 91.3% and 89.2% of strains, respectively. These findings are in agreement with previous studies (Kwag et al, 2008;Hur et al, 2011;Huehn et al, 2010;Bolton et al, 2011), which have also reported the high prevalence of spvC and rck genes in salmonella isolates. A self-transferable virulence-resistance plasmid (pUO-StVR2) carrying the spvA, spvB, spvC, and rck gene was earlier reported in S. Typhimurium (Guerra et al, 2002).…”
Section: Discussionsupporting
confidence: 94%
“…However, PT4 has not appeared in the literature since that time [11,28,29]. Recently, Kang et al [24] reported PT1 and PT21 accounted for 27.2% and 20.8%, respectively; however, PT4 has been found in only 8.7%.…”
Section: Discussionmentioning
confidence: 99%